DOMINATION RIBAWI TRANSACTIONS IN THE ECONOMY - Dyarini Dyarini (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2017)
ABSTRACT. Though the fight against usury command is a cornerstone ofIslamic finance but the debate about the significance of the word